DAMPAK PEMBELAJARAN JARAK JAUH TERHADAP KONSEPSI SISWA KELAS XII SMK PADA MATERI STATISTIKA - Melisa Melisa; Rafiq Zulkarnaen (IKIP Siliwangi, 2022)
The limitations of distance learning are thought to cause students to have difficulty understanding mathematics, especially statistics. This study aims to analyze the impact of distance learning on students' conceptions of statistical material. An exploratory case study was used in this study, with a single case and single analysis. In this study, students had difficulty in solving statistical problems during distance learning, while a single analysis was used to examine the factors causing difficulties from the impact of distance learning. The research subjects were 68 students in two class XII AKL at one State Vocational School in Karawang Regency. Test and non-test instruments were used in this study, five questions were explained in statistics material and structured interviews about the impact of distance learning. The indicator of difficulty on statistical questions with high criteria concluded that 73% of students had difficulty in explaining ideas, situations, and mathematical relationships orally and in writing on statistical material. This is because students find it difficult to understand the material, explain and analyze the data given in the problem or problem. These findings were obtained as a result of the lack of direct learning interaction in mathematical activities when online or offline.